NEW BRYOZOAN SPECIES OF THE FAMILY ATACTOTOECHIDAE FROM THE DEVONIAN OF TRANSCAUCASIA - Lavrentjeva V.D. (My University, 2001)
Five new species of trepostomid bryozoans are described from the Middle and tbe Upper Devonian of Transcaucasia: Schulgina ulilinae, Leptotrypa simplex, Leptotrypa dansikensis, Ataclotoeclms interruptus and Anomalotoeclms pewulgatiis (all family Atactotoechidae).
Keywords: Devonian; Bryozoan; Transcaucasia; Paleozoic::Devonian; Палеозой::Девонская